Structural and mechanistic insights into Mycothiol disulfide reductase, Mycoredoxin-1 and peroxiredoxin alkyl hydroperoxidase subunit E of Mycobacterium tuberculosis - Kumar, Arvind (2017)
Mycobacterium tuberculosis (Mtb) has the ability to persist within the human host for a long time in a dormant stage and re-emerges when the immune system is compromised. During infection, Mtb is exposed to a number of redox stresses inside macrophages, such as reactive oxygen species and reactive nitrogen intermediates, both having the potential to damage a number of cellular components, including lipids, proteins, and DNA [1]. The ability of Mtb to persist inside macrophages suggests the presence of elaborated machineries capable of preserving redox homeostasis and countering oxidoreductive stress. Mtb is equipped with sophisticated proteins and thiols (mycothiol) responsible for antioxidant defense. Most of these proteins as well as mycothiol are unique to mycobacteria and therefore lacking in the human host, like the mycothiol-dependent system composed of the enzymes mycothione reductase (Mtr), myco-redoxin1 (Mrx-1), and the alkyl hydroperoxidase subunit E (MtAhpE), responsible for the reduction of hydrogen peroxide, peroxynitrous acid, organic peroxides or S-mycothiolated mixed disulfides, generated by oxidative stress. Clearly, the protein ensemble and mycothiol of the antioxidant defense of Mtb differ substantially from that in the mammalian hosts and thus the chances for a selective inhibition of the mycobacterial antioxidant defense system will be high. In the effort to understand the biological mechanisms of the mycobacterial antioxidant defense orchestra, this work aims to provide structural, enzymatic and mechanistic insights into the Mtb NADPH dependent Mtr (MtMtr), structural details of Mtb Mrx-1 (MtMrx-1) and AhpE (MtAhpE) as well as mechanistic insights into the mycothiol/Mrx-1 dependent recycling of peroxiredoxin MtAhpE. In the first part of this thesis, the production of a stable MtMtr using a GroEL/ES chaperone-chaperonin system is described. The recombinant MtMtr provided a platform for the first low resolution solution structure by small-angle X-ray scattering (SAXS), representing a dimeric enzyme. Substrate induced conformational changes of MtMtr in the presence of NADPH and mycothiol were studied in solution by SAXS, demonstrating significant overall changes after NADPH-binding, interpreted by a shift of a dimeric to a tetrameric form of the NADPH-bound MtMtr. Genetically engineered mutants of MtMtr shed light into the importance of the flexibility of the linker, connecting the catalytic FAD-domain I with the NADPH-domain, as well as the linker, connecting the NADPH- with the FAD-domain II. Furthermore, attempts were made to crystallize MtMtr, resulting in needle showers. Together, with the linker mutants generated, these may provide a platform for crystallization approaches in the near future. Together with the generation of recombinant MtMrx-1, which was revealed to be monomeric in solution regardless of the redox state and concentration, the ensemble formation of MtMtr and MtMrx-1 was studied by NMR titration. The MtMtr-MtMrx-1 interaction was characterized by a fast exchange regime and critical residues involved in the protein-protein interaction were identified. In order to shed light into the complete ensemble of the the mycothiol-dependent system, recombinant MtAhpE was produced and purified. Its ensemble formation with MtMrx-1 was analysed by NMR spectroscopy and docking studies, providing insights into the interaction interface and mechanism of action. The interaction model presented revealed, that two molecules of monomeric MtMrx-1 interact with one dimeric MtAhpE with each molecule of MtMrx-1 reducing one monomer of MtAhpE. The last chapter describes in detail the structural and mechanistic characterisation of MtAhpE. The oligomeric state of MtAhpE was shown to be a dimer regardless of the redox condition. Interestingly, the formation of a higher molecular weight oligomer was indicated in dynamic light scattering and SAXS studies in the presence of equimolar H2O2. Using cysteine-labelling NMR experiments, it was possible to investigate the redox dynamics of the catalytic and peroxidatic cysteine in solution in the presence of various reducing agents. These data enabled to propose a new monothiolic pathway for the reduction of MtAhpE by mycothiol in the absence of MtMrx-1. Finally, the crystallographic structures of MtAhpE in the presence of mycothiol (2.43 Å resolution) and the mycothiol-analogue N-acetylcysteine (2. 2.7 Å resolution) were determined, respectively, to validate the newly proposed pathway in depth.